Reindeer as Draught Animals in Tourism: Bringing Past Traditions into Modern Practices - Soppela, Päivi; Kynkäänniemi, Sanna-Mari; Wallén, Henri; Salmi, Anna-Kaisa (The Arctic Institute of North America, 2024)
Driving with reindeer is an old tradition in northern Fennoscandia that became almost extinct in the last century but that has increased in the past few decades along with tourism. This study investigates the current use of draught reindeer in Lapland, identifies changes since the mid-1900s, and explores the human-reindeer relationship related to this practice, including draught training. We conducted interviews and participatory research with 15 reindeer herders who trained draught reindeer for tourism and competitive racing in northern Finland. Reindeer training today follows similar steps to those followed in the last century, but today the draught training starts earlier, with calves in their first autumn, and takes longer, usually three to four winters. The reindeer are carefully chosen, and their training and roles are more specified than in the past. Mutual trust, communication, and learning play essential roles in the establishment of human-reindeer relationships and collaboration. Herders treat reindeer as individuals and co-actors and take into account their interests and well-being. Driving practice was restarted in the 1970s because of tourism. In the early years of tourism, when draught reindeer were not available for this, racing reindeer were used for sledging; this contributed to the revival of the practice. We conclude that draught reindeer training and use in tourism is reviving old draught-reindeer culture and passing it forward, albeit in a new form. It combines reindeer herders’ traditional knowledge with modern requirements, deepens the herder-reindeer relationship, and supports reindeer herding as a livelihood. En Fennoscandie, conduire des rennes est une ancienne tradition qui s’est presque éteinte au cours du dernier siècle, mais qui a pris de l’ampleur ces dernières décennies grâce au tourisme. Cette étude porte sur l’usage actuel des rennes de trait en Laponie, cerne les changements qui se sont produits depuis le milieu des années 1900 et explore la relation entre les humains et les ...